ATNESA workshop stimulates regional cooperation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Improving animal traction technology The first workshop of the Animal Traction Network for Eastern and Southern Africa was held from 18-23 January, 1992, in Lusaka, Zambia.